A Critique of “Prehistoric Mesopotamia” - rahmat abbasnejadseresti (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Southwest Asia has a great importance in Prehistoric Archaeology. The region of the Fertile Crescent, in which sedentism and domestication have been adopted by humankind for the first time, is located in this region. Mesopotamia is one of the most important parts of this region and has a special role in livelihood, economic, and social events of prehistoric times. The present paper, in line with the critical approach to academic teaching books, criticizes the form and content of the book of Prehistoric Mesopotamia written by Dr. Hassan Talaei, published by the Organization for Researching and Composing University Textbooks in the Humanities (SAMT). Like any other work, this book has some advantages and disadvantages. The most desirable feature of the book is the relatively comprehensive information from the prehistoric of Mesopotamia that is readily accessible to the reader by a fluent and comprehensible text.The universality of the book in terms of its components is one of its most obvious drawbacks. The useful and relatively descriptive discussions that are presented in the book are not crystallized in the index. The tables, images and maps used in the book do not have enough desirability. The empty compilation and conclusion is completely evident in the book. The lack of analysis of archaeological data and the lack of critique of the Mesopotamian prehistoric theories are the most important book flaws.The periodization of the Neolithic period has not taken place in a specific framework; therefore, the reader of the book can hardly grasp the exact understanding of the Neolithic periods and their evolution whereas the Epi-Palaeolithic, Proto-Neolithic and Neolithic periods of the Levant and Mesopotamian regions were precisely categorized since 1990 decade. Archaeological theories of prehistoric cultures of the Mesopotamian lands have also not been criticized in the book. The author of the book should devote a discussion to the status of the Economic-social Complexities of North and South of Mesopotamia during the Chalcolithic period and Bronze Age.